Architects' Cognitive Behaviour in Parametric Design. (March 2015) - Yu, Rongrong; Gero, John; Gu, Ning
This paper presents the results of a protocol study of professional architects' cognitive behaviour in a parametric design environment. A design experiment was conducted in which eight professional architects completed an architectural conceptual design task in a typical parametric design environment –Rhino and Grasshopper. Protocol analysis was then applied to analyse the cognitive behaviour of the architects. In analysing the protocol data, the FBS ontology adopted for developing the coding scheme was sub-divided into design knowledge and rule algorithm classes as the means to capture designers' cognitive behaviour. Applying the method of cumulative analysis, results of the relative cognitive effort expended on design knowledge and rule algorithm classes have been compared and are discussed in the paper.